Clothing polymer fibers with well-aligned and high-aspect ratio carbon nanotubes - Sun, Gengzhi (2016)
It is believed that the crucial step towards preparation of electrical conductive polymer–carbon nanotube (CNT) composites is dispersing CNTs with a high length-to-diameter aspect ratio in a well-aligned manner. However, this process is extremely challenging when dealing with long and entangled CNTs. Here in this study, a new approach is demonstrated to fabricate conductive polymer–CNT composite fibers without involving any dispersion process. Well-aligned CNT films were firstly drawn from CNT arrays, and then directly coated on polycaprolactone fibers to form polymer–CNT composite fibers. The conductivity of these composite fibers can be as high as 285 S m−1 with only 2.5 wt% CNT loading, and reach 1549 S m−1 when CNT loading is 13.4 wt%. As-prepared composite fibers also exhibit 82% retention of conductivity at a strain of 7%, and have improved mechanical properties.